PENGARUH DISPOSISI MATEMATIS TERHADAP PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA SMK DI KOTA CIMAHI KELAS X - Dita Mariyanti Dewi; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze and examine in depth the effects of mathematical disposition on learning based learning on vocational students in Cimahi City CLASS X. The method in this study uses a correlation method with a quantitative approach. The population in this study were SMK Pusdikhubad Cimahi students and the samples were students of class X TSM B with a total of 34 students. In this study to find out the disposition of students towards mathematics, can it be done with confidence, responsibility, diligence and willingness of students to find other ways to solve the mathematical problems given. The instrument in this study was a test of Probelem Based Learning learning outcomes of 5 items and a mathematical disposition scale of 30 statement scales. The results of this study concluded that, the learning outcomes of Problem Based Learning which were influenced by students 'mathematical dispositions amounted to 79.7% while 20.3% were influenced by factors outside of students' mathematical dispositions.